LIMITATIONS OF THE PLURALITY SYSTEM IN THE ELECTION OF THE PRESIDENT OF THE REPUBLIC OF SRPSKA: POLITICAL, INSTITUTIONAL AND SOCIAL CONSEQUENCES - Vukojević, Stefan (Srpska politička misao, 2025)
This paper analyzes the political, institutional, and social consequences of applying the plurality (first-past-the-post) electoral system for the election of the President of the Republic of Srpska. The goal is to assess how well this electoral model meets the democratic needs of an ethnically divided, post-conflict society and to propose recommendations for potential reform to strengthen democratic legitimacy and political stability. The analysis relies on a comparative case study of presidential elections in the Republic of Srpska, drawing on theoretical literature on electoral systems in divided societies. The findings show that the plurality system undermines the legitimacy of the elected president, fuels political polarization, ethnic mobilization, and personalized leadership, while reducing incentives for political compromise. As alternatives, the paper considers a two-round majority system and preferential voting, which could encourage more moderate political discourse and broader social support. It concludes that changing the electoral model could enhance both legitimacy and political stability in the Republic of Srpska.